Perceived barriers to food packaging recycling: Evidence from a choice experiment of US consumers. (March 2017) - Klaiman, Kimberly; Ortega, David L.; Garnache, Cloé
Abstract: To increase recycling rates, packaging companies, policymakers, and food and beverage companies have promoted recycling of packaging through media and packaging labels. Yet, how effective such information is at enhancing recycling behavior remains subject to debate. This study contributes to the literature on product recycling by examining how particular packaging characteristics foster or hinder recycling. An online survey administered to a representative sample of 1500 American households is used to examine consumer perceived barriers to recycling food packaging. Using a between-subject choice experiment design, we investigate the effectiveness of message targeting and media delivery, including infographic and video treatments, on consumer stated recycling behavior of a plastic or boxboard sandwich container. We find that respondents viewed having to clean packaging, a requirement for many food products, as a barrier to recycling, but not the type of packaging material or the number of steps involved in recycling the product. Individuals drawn to recycling for energy conservation reasons were less likely to view cleaning as a barrier. The information treatments did not significantly affect consumer recycling behavior, however, they altered preferences for packaging material. Highlights: We test for the effectiveness of information on recycling behavior. Consumers view having to clean packaging as a major barrier to recycling. Two groups of consumers with different preferences towards recycling were identified. Information was shown to alter consumer preferences for packaging material.